Educational and Social Challenges Facing University Students with Disabilities (Damascus University Journal of educational and Psychologyical sciences, 2024)
The current study aimed to reveal the level of severity of the educational and social challenges facing students with disabilities at Damascus University during their academic career. In addition, it aimed to investigate the effect of each of the following variables ( sex, type of disability, faculty. And school year) on the level of severity of the educational and social challenges faced by the students. The study sample consisted of 50 male and female university students who suffer from one of the following disabilities ( hearing, visual, or movement) and who are enrolled in one of the following faculties at Damascus University ( Education, Arts, Law, Economics) during the first semester of the year 2022/2023. In order to achieve the study objectives, a questionnaire was designed to measure the educational and social challenges faced by the disabled students. The results showed that the level of severity of the educational and social challenges faced by Damascus University students regarding all questions was on the medium degree. Moreover, the results indicated that there were no statistically significant differences on the level (5%) of the severity level of the educational and social challenges faced by disabled students at Damascus University related to any of  the variables ( sex, type of disability, faculty, and school year).
Keywords: Educational Challenges; Social Challenges; University Students With Disabilities.